Substantiation of the professiographic model of sports dances - Olha Podrihalo; Guo Xiaohong; Leonid Podrigalo; Olexandr Podavalenko; Olexsandr Halashko (Kharkiv State Academy of Physical Culture, 2022)
Purpose:analysisoftheactivityofdancesportathletesusingprofessiographic techniques to optimize the training and growth of sportsmanship. Material & Methods: the method of developing a professiogram was used according to the accepted methodology, methods for assessing the severity and intensity of work were used. results: the severity and intensity of sports activities in dancing were assessed. The main professional requirements are identified, which include: the need to maintain a pose in dance, high technicality in performing elements, mandatory artistry, a sense of rhythm and performing movements in accordance with music, high noise immunity, high physical preparedness with an advantage in coordination, strength qualities and endurance, high functionality of cardiorespiratory systems. conclusions: the analysis of sports activities in sports dances made it possible to substantiate and develop a professional model of this sport. It has been established that sports dances belong to the 3rd category of labor in terms of severity and the 4th category in terms of intensity in accordance with the official physiological and hygienic criteria. The main professional requirements that determine the success of professional activity are highlighted. A set of methods necessary for the study and assessment of the state of the most important organs and systems that ensure the implementation of sports tasks is substantiated. These methods can be used in monitoring the functional state of athletes to develop a forecast for the growth of sportsmanship